Fibrous structure in the intervertebral disk: correlation of MR appearance with anatomic sections. - Yu, S W; Haughton, V M; Lynch, K L; Ho, K C; Sether, L A (American Journal of Neuroradiology, 1989)
To correlate the MR appearance of the disk with its fibrous structure, we studied the lumbar intervertebral disks in 10 cadavers with MR, CT, cryomicrotome anatomic sections, and, in selected disks, with histologic and dried sections. In MR images the predominantly fibrous tissues such as Sharpey's fibers had a low signal intensity while the fibrocartilagenous tissues with a mucoid matrix in the intervertebral disk had a high signal intensity. In the equator of the adult disk was a well-defined fibrous plate that contained collagenous, elastic, and reticular fibers with little ground substance. This plate appeared to develop progressively from the periphery of the nucleus toward the center, starting in the second decade of life. The fibrous plate was also distinguished as a lower signal intensity in the MR images.